Análisis de los ingresos de la Finca Bananera San Jacinto - Lara Astudillo, Glenda Magaly (2017)
An agricultural survey conducted in 2015 by the Instituto Nacional de Statistics and Censuses showed that the Province of Los Ríos is the third province with greater production of bananas and cacao as it is located in the coastal region of Ecuador. The banana growers in Ecuador obtain income according to their production with established price by the Ministry of Agriculture, Livestock, Aquaculture and Fisheries, establishing limits for both parties as well as for the banana exporter and producer. In this way we announce that the topic to be developed in this research is called ANALYSIS OF BANANAS INCOME OF THE FINCA SAN JACINTO, an investigation that was carried out in said Finca which has 17 years of experience in the banana sector producing an approximate 44000 boxes of banana per year in two banana varieties. This case study is carried out to analyze the income that the farm maintains due to the differentiation of income through invoicing and income to the bank account, the which must carry a rigorous income control in addition to adherence to the framework of the law. Ecuador leads the list of countries with quality banana exports according to page Fresh Plaza ranks it with 40.6% as the main exporter in the world in the year 2016; the banana plantations as such fulfill an important range within the economy Ecuadorian because it is the second source of non-oil revenue for the state; generating a contribution to gross domestic product, as well as foreign exchange, and in terms of to the generation of jobs. In 2016, banana exports were around 32.1% according to Bulletin No. 1918 of the Central Bank of Ecuador, still occupying the second place of income has declined for climate reasons Ecuadorian coasts, the international trade agreements, in addition to the growth in productions from countries such as Costa Rica, Colombia, the Caribbean, etc.